Towards a Unique Archive of Aboriginal Languages: A Collaborative Project*. Issue 1 (2nd January 2017) - Mamtora, Jayshree; Bow, Catherine
Abstract: Charles Darwin University Library is directly helping to sustain and preserve Aboriginal language and cultural materials that encounter many hurdles for their long-term survival. The library is supporting an ARC-funded project known as the Living Archive of Aboriginal Languages, by providing a repository, web application, digitisation programme and professional advice. The collaboration between the library and research team addressed a number of challenges in relation to appropriate ways to represent complex and variable metadata, widely varying content from diverse sources and in various conditions, and in making these fragile and endangered materials accessible to a global audience. The open access archive now includes thousands of items in dozens of Northern Territory Indigenous languages, providing a sustainable repository for researchers and allowing Indigenous communities to share their languages, histories, knowledge and practices around the world. The project serves as a rich case study demonstrating how academic libraries can work with researchers to support the archiving of cultural heritage.